The Effect of Yeast Strain, Immobilisation, and Ageing Time on the Amount of Free Amino Acids and Amino Acids in Peptides of Sparkling Wines Obtained from cv. Dimrit Grapes - BozdoÄŸan, A.; CanbaÅŸ, A. (South African Journal of Enology and Viticulture, 2016)
In this study, the influence of yeast strain, immobilisation, and ageing time with yeast were examined in relation to the amount of free amino acids and amino acids in the peptides of wines. Free and immobilised Saccharomyces bayanus and Saccharomyces cerevisiae yeasts were used in sparkling wine production. Samples from the base wine and sparkling wines were taken at 20, 40, 90, 180, 270 and 365 days of ageing with yeast. It was observed that the majority of differences between wine samples in terms of the amount of free amino acids and amino acids in peptides were due to ageing time. The amount of total free amino acids in wine made with Saccharomyces cerevisiae was higher than in that made with Saccharomyces bayanus. In addition, no differences were observed between free and immobilised yeast in terms of amino acids and amino acids in peptides.